Morbidity of contagious syphilis in the past six years - Loret de Mola, A. (1956)
In the course of this year we have seen with great surprise that the number of patients with early syphilis lesion, increased by growing form which undoubtedly led us to make a detailed study about choosing two centers of high turnout in adults and different location "Workers Hospital Obrero de Lima and Callao Policlinico" patients, who were diagnosed in a period of four months 220 cases of primary syphilis, confirmed by the presence of treponemes in dark field, the main focus of pollution-called red light district of Victoria.